1999
DOI: 10.1002/(sici)1521-3919(19990501)8:3<272::aid-mats272>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

A DFT quantum-chemical study on the structures and active sites of polymethylaluminoxane

Abstract: SUMMARY:The electronic structure and geometry of polymethylaluminoxane (MAO) [ 1Al(CH 3 )O1 ] n with different size (n = 4 -12) have been studied using quantum-chemical DFT (density functional theory) calculations. It has been found: 1) Starting from n = 6, the three-dimensional oxo-bridged (cage) structure of MAO is more stable than the cyclic structure. 2) Both for cage structure and for cyclic structure the Lewis acidity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 24 publications
5
45
0
1
Order By: Relevance
“…Quantum chemical calculations based on the density functional theory (DFT) for drum-like or cyclic (MeAlO) n oligomers showed that three-dimensional cage structures are more stable than cyclic ones. [14] On the grounds of multinuclear NMR studies, a better understanding of the MAO structure could be obtained. [27] Al NMR analysis of MAO at temperatures ranging from room temperature to 120 8C indicates that the Al resonance in MAO appears at 110 l 10 ppm and in TMA at 149 -153 ppm.…”
Section: Molar Massmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantum chemical calculations based on the density functional theory (DFT) for drum-like or cyclic (MeAlO) n oligomers showed that three-dimensional cage structures are more stable than cyclic ones. [14] On the grounds of multinuclear NMR studies, a better understanding of the MAO structure could be obtained. [27] Al NMR analysis of MAO at temperatures ranging from room temperature to 120 8C indicates that the Al resonance in MAO appears at 110 l 10 ppm and in TMA at 149 -153 ppm.…”
Section: Molar Massmentioning
confidence: 99%
“…[14] In a recent series of density functional calculations, an Me 18 Al 12 O 9 cage structure of correct Me/Al ratio with C 3h symmetry was suggested as a model for MAO. [24] In this model, the cage is rigid but bridging methyl groups are labile and reactive.…”
Section: Molar Massmentioning
confidence: 99%
See 1 more Smart Citation
“…[13,14] for tert-butylaluminoxane of composition [(t-Bu)Al(l 3 -O)] n , (n = 6,9). In other work [15,16] a quantum-chemical DFT method was used to calculate the geometry and electronic structure of MAO with various molecular masses (oligomerization degree n = 4-12), and analyze how the oligomerization degree affects the MAO structure and acidic properties. For MAO with n F 6 the cage structure proved to be the most stable.…”
Section: Introductionmentioning
confidence: 64%
“…Além disso, Zakharov e colaboradores 39,40 , com base em resultados de simulação por DFT ("Density functional theory"), propuseram um mecanismo de formação da espécie reativa de metilaluminoxano, responsável pela ativação do catalisador (Figura 4). O mecanismo está baseado na interação do dímero do trimetilalumínio com o metilaluminoxano, que leva à formação da estrutura II, seguido da formação da estrutura III de maior acidez, que atua como cocatalisador.…”
Section: Efeito Do Cocatalisadorunclassified